Spiritual intelligence and psychological well-being in refugees - Lee-Fong, Gillian (Mental health, religion & culture, 2022)
Refugees share a common bond in the premigration, migration, and postmigration stressors they have experienced. Despite these adverse circumstances, many refugees are able to recover, regain psychological wellness, and live productive lives. While previous research has revealed links between psychological well-being and spiritual intelligence, to date, no such research has examined these variables in refugee populations in the United States. The present study examined the empirical relationship between spiritual intelligence and psychological well-being in a diverse sample of refugees (N = 76). The relationship between spiritual intelligence and psychological well-being yielded a significant correlation while moderating variables (years living in the US and number of traumatic events) did not impact this relationship. As refugee populations continue to grow, findings from this study may be beneficial for guiding mental health professionals in developing more culturally appropriate, holistic treatment plans to effectively address trauma and build resilience in refugees.